Association between the survey-based women's empowerment index (SWPER) and intimate partner violence in sub-Saharan Africa - Irene Esi Donkoh; Richard Gyan Aboagye; Joshua Okyere; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Sanni Yaya (BMC, 2024)
Abstract Background Intimate partner violence (IPV) is high among women of reproductive age in sub-Saharan Africa (SSA). However, empowering women enables them to confront and mitigate IPV. In this study, we examined the association between the survey-based women's empowerment index (SWPER) and IPV in SSA. Methods We used data from the Demographic and Health Surveys of 19 countries conducted from 2015 to 2021. Our study was restricted to a weighted sample of 82,203 women of reproductive age who were married or cohabiting. We used spatial maps to show the proportions of women who experienced past-year IPV. A five-modelled multilevel binary logistic regression analysis was adopted to examine the association between SWPER and IPV. The results were presented using the adjusted odds ratio (AOR) with their respective 95% confidence interval (CI). Statistical significance was set at p < 0.05. Results With physical and emotional violence, the country with the highest prevalence was Sierra Leone, with a prevalence of 39.00% and 38.97% respectively. Rwanda (10.34%), Zambia (11.09%), Malawi (15.00%), Uganda (16.88%), and Burundi (20.32%) were the hotspot countries for sexual violence. Angola (34.54%), Uganda (41.55%), Liberia (47.94%), and Sierra Leone (59.98%) were the hotspot countries for IPV. A high SWPER score in attitudes to violence significantly decreased the odds of IPV [AOR = 0.70; 95% CI = 0.66, 0.75]. Also, women with medium score in decision-making were less likely to experience IPV compared to those with lower scores [AOR = 0.89; 95% CI = 0.83, 0.95]. However, higher odds of experiencing IPV was found among women with medium score in autonomy compared to those with low scores [AOR = 1.07; 95% CI = 1.01, 1.14]. Conclusions Our study has shown that the three dimensions of SWPER significantly predict IPV among women. Consequently, it is crucial that sub-Saharan African countries implement various initiatives, such as IPV advocacy programs and economic livelihood empowerment initiatives. These initiatives should not only aim to improve women's attitudes to domestic violence but also to enhance their social independence, autonomy, and decision-making capacity.